2013
DOI: 10.1007/s10802-013-9717-0
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Beliefs about Aggression, Implicit Knowledge Structures, and Teen Dating Violence

Abstract: This study examined whether explicit beliefs justifying aggression and implicit knowledge structures theorized to facilitate aggression both contributed to between-subjects differences in teen dating violence (TDV). In addition, this research examined the contribution of explicit and implicit cognitions in the prediction of within-subjects changes in TDV over a 6-month period. Participants were 147 14- to 17-year-olds (48 % female) recruited from courts and agencies providing services to adolescents in trouble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Second, all data were self-report and, as such, social desirability bias may have influenced survey responses. Some research suggests that social desirability bias may be addressed through the use of implicit measures (e.g., the Implicit Association Test) of normative beliefs and gender role attitudes that assess unconscious attitudes and beliefs (Eckhardt et al 2012); this is a promising direction for future dating violence research with adolescents (Jouriles et al 2013). Third, based on our theoretical framework, the current study focused on male perpetration of physical dating violence.…”
Section: Discussionmentioning
confidence: 99%
“…Second, all data were self-report and, as such, social desirability bias may have influenced survey responses. Some research suggests that social desirability bias may be addressed through the use of implicit measures (e.g., the Implicit Association Test) of normative beliefs and gender role attitudes that assess unconscious attitudes and beliefs (Eckhardt et al 2012); this is a promising direction for future dating violence research with adolescents (Jouriles et al 2013). Third, based on our theoretical framework, the current study focused on male perpetration of physical dating violence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the abovementioned EMSs, the justification of violence schema has been consistently related to aggressive behavior (e.g., Burton, Florell, & Wygant, 2013; Huesmann & Guerra, 1997; Jouriles, Rosenfield, McDonald, Kleinsasser, & Dodson, 2013). This schema, which is not part of the schema theory, refers to the normative appropriateness of aggressive behavior (Huesmann & Guerra, 1997).…”
Section: Emss Sip and Cpamentioning
confidence: 99%
“…Minimal research has also been conducted on whether the acceptability of IPV is differentially related to one’s own IPV perpetration based on race or ethnicity. Indeed, despite prior research utilizing diverse samples of adolescents (e.g., Jouriles, Rosenfield, McDonald, Kleinsasser, & Dodson, 2013; Orpinas et al, 2013; Temple et al, 2016), studies have largely ignored whether the association between acceptability of IPV and one’s own IPV perpetration differs across racial or ethnic groups. Preliminary research with adults has demonstrated that Hispanic women, relative to non-Hispanic women, are significantly more likely to agree that there are times when slapping a partner is acceptable (Ingram, 2007).…”
Section: Gender Race/ethnicity and Acceptability Of Violencementioning
confidence: 99%